Advanced analysis and learning on temporal data : first ECML PKDD Workshop, AALTD 2015, Porto, Portugal, September 11, 2015, Revised selected papers /: first ECML PKDD Workshop, AALTD 2015, Porto, Portugal, September 11, 2015, Revised selected papers. (2016) - Unknown
No abstract available